The influence of educational service quality, trust on the loyalty of students of Private Junior High School "X", Bandung City - Douwes, Cornelia; Saputra, Bobby Wiryawan (Indonesian Journal of Multidisciplinary Science, 2024)
The purpose of this study is to determine the influence of the quality of educational services on student loyalty, the influence between trust and student loyalty and the influence on the service quality through student trust in Private Junior High School (SMP) "X" Bandung City. The results of the study show that there is a positive and significant influence on trust with a total influence of 70.9%, 64.8%, 31.6%, and 96.3%, respectively. In addition, there is an influence of trust mediated by trust on the loyalty of students at SMP "X."